Impact of Gangasagar Mela on Sustainability of Sagar Island, West Bengal, India - Hajra Rituparna; Mitra Rajarshi; Ghosh Tuhin (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Sagar Island, the largest delta of Sundarbans island complex with an area of nearly 240 sq. km. and with 1.60 lakh population, defines the south-west boundary of Sundarbans. Due to the complex interplay of natural dynamics and human intervention, the sustainability of the island is under threat. Sagardwip, a densely populated island, always faces impacts of adverse anthropogenic activities and socio-ecological practices. A balancing mechanism of environmental management of the coastal zone is therefore an important issue for its sustainability. In reality, the annual gathering in Gangasagar Mela (GSM) – a famous religious Hindu festival, one of the major income generating activities of the island dwellers frequently imposes public health problem in form of organic pollution of the water bodies. Sometimes it leads to socio-economic instability also. In this present work a pilot study has been carried out to estimate the pollution potential of the annual gathering on water bodies in and around Sagar Island including Bay of Bengal. Comparison of pre- and post- gathering water samples shows a tendency of tremendous water quality degradation, especially in respect to the organic pollution, which can be easily accounted by total and fecal coliform bacteria count. One to one interview of local residents and health workers too confirmed the public health problems subjectively. The site specific nature of degradation has clearly indicated that the worst source of pollution is the festival ground itself. However, a thorough environmental impact assessment of the area is needed to make a judgment on the effects of such religious gathering to maintain an overall sustainability of the coastal zone.